ANALISIS KREDIT BERMASALAH PADA KOPERASI BUMDes MUARA UWAI SEJAHTERA KECAMATAN BANGKINANG SEBERANG KABUPATEN KAMPAR - Arna Kartika; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study discusses to study and discuss credit at the BUMDes Muara Uwai Sejahtera Kampar Cooperative during the 2014-2018 period. This study uses secondary data consisting of data obtained by the author through, manual reports and financial statements of the Muara Uwai Sejahtera Kampar Cooperative BUMD that are needed by researchers for reliable credit analysis. This research uses descriptive qualitative. Data collection was obtained from interviews and documentation. Checking the validity of the findings using source triangulation so that it is easy to analyze various problems that occur in the company. The conclusions of this study are (1) The credit granting procedure applied by the Muara Uwai Sejahtera BUMDes Cooperative is in accordance with the guidelines for providing healthy credit but has a deficiency in the credit assessment analysis section. (2) The development of Non-Performing Loans at Muara Uwai Sejahtera BUMDes Cooperative during the last 5 (five) years has increased. (3) factors from debtors and internal factors of cooperatives that cause problem loans at the Muara Uwai Sejahtera BUMDes Cooperative (4) settlement of problem loans that have been implemented, namely routine billing, credit restructuring. Keywords: non-performing loans, causes of problem credit, problem credit settlement